Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada PT. Deli Wijaya Sakti Di Samarinda - suarno; marten apuy; Chundra Siewanto (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2026)
The research question is, "Do product quality and service quality jointly influence customer satisfaction at PT. Deli Wijaya Sakti in Samarinda?" The sample size for this study was 95 respondents, all of whom were customers at PT. Deli Wijaya Sakti in Samarinda. Data collection methods included observation, interviews, questionnaires, and documentation. The analytical tools used in this study were multiple linear regression analysis, partial correlation coefficients, multiple correlation coefficients, and coefficients of determination. Hypothesis testing used the t-test and F-test, processed using IBM SPSS version 25. The results of the Multiple Linear Regression analysis are Y = 5.374 + 0.324 (X1), + 0.321 (X2). This equation indicates that Product Quality (X1) and Service Quality (X2) influence Customer Satisfaction (Y). From the results of the t test for the independent variable, namely Product Quality, obtained t count (4.353) > (1.986), and the significance value of t (0.000) < 0.05, which means that Product Quality has a partial effect on Consumer Satisfaction at PT. Deli Wijaya Sakti in Samarinda. For the independent variable, namely Service Quality, obtained t count (3.262) > (1.986), and the significance value of t (0.002) < 0.05, which means that Service Quality has a partial effect on Consumer Satisfaction at PT. Deli Wijaya Sakti in Samarinda. Meanwhile, from the results of the F test for the independent variables of Product Quality and Service Quality, obtained F count value (69.401) > F table (3.095), and the significance value of F (0.000) < 0.05, which means that Product Quality and Service Quality have a joint effect on Consumer Satisfaction at PT. Deli Wijaya Sakti in Samarinda.